Speaking fundamental frequency of original speakers and their imitators - MAJEWSKI, Wolciech (Archives of Acoustics, 2007)
The results of SFF measurements of well-known Polish personalities and their imitations performed by cabaret entertainers are presented and discussed. The difference in F0 between the original speakers and their imitators was in some cases few Hz only, but in some other cases it reached more than 100 Hz.